An introduction to rapid system prototyping. - Kordon, F.
The implementation and maintenance of industrial applications have continuously become more and more difficult. In this context, one problem is the evaluation of complex systems. The IEEE defines prototyping as a development approach promoting the implementation of a pilot version of the intended product. This approach is a potential solution to the early evaluation of a system. It can also be used to avoid the shift between the description/specification of a system and its implementation. This brief introduction to the special section on rapid system prototyping illustrates a current picture of prototyping.
Keywords: Pilot version; Rapid system prototyping; System description